2022
DOI: 10.1021/acsptsci.1c00238
|View full text |Cite
|
Sign up to set email alerts
|

Development of Inhaled GABAA Receptor Modulators to Improve Airway Function in Bronchoconstrictive Disorders

Abstract: We report the modification of MIDD0301, an imidazodiazepine GABA A receptor (GABA A R) ligand, using two alkyl substituents. We developed PI310 with a 6-(4-phenylbutoxy)hexyl chain as used in the long-acting β2-agonist salmeterol and PI320 with a poly(ethylene glycol) chain as used to improve the brain:plasma ratio of naloxegol, a naloxone analogue. Both imidazodiazepines showed affinity toward the GABA A R binding site of clonazepam, with IC 50 values of 576 and 242 nM, respectively. Molecular docking analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
(88 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, hydrogen bond interactions between the carboxylate and Ser206 and Ser205 and the imine function were identified. We reported molecular docking poses for MIDD0301 bearing a (R) or (S) methyl substituent instead of the cyclopropyl substituent and observed the almost same docking poses . The stereochemistry of the methyl substituent did not significantly influence GABA A R binding ( MIDD0301 (IC 50 = 26 nM) and MIDD0301S (IC 50 = 25 nM)).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, hydrogen bond interactions between the carboxylate and Ser206 and Ser205 and the imine function were identified. We reported molecular docking poses for MIDD0301 bearing a (R) or (S) methyl substituent instead of the cyclopropyl substituent and observed the almost same docking poses . The stereochemistry of the methyl substituent did not significantly influence GABA A R binding ( MIDD0301 (IC 50 = 26 nM) and MIDD0301S (IC 50 = 25 nM)).…”
Section: Resultsmentioning
confidence: 86%
“…We previously reported that MIDD0301 potently relaxes constricted airway smooth muscle ex vivo and reduces AHR in vivo. ,,, For the ex vivo experiment, guinea pig tracheal rings were suspended in an organ bath, constricted with substance-P, and treated with 5a–j followed by recording of muscle force (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation